DialBetics: A Novel Smartphone-based Self-management Support System for Type 2 Diabetes Patients. (March 2014) - Waki, Kayo; Fujita, Hideo; Uchimura, Yuji; Omae, Koji; Aramaki, Eiji; Kato, Shigeko; Lee, Hanae; Kobayashi, Haruka; Kadowaki, Takashi; Ohe, Kazuhiko
Numerous diabetes-management systems and programs for improving glycemic control to meet guideline targets have been proposed, using IT technology. But all of them allow only limited—or no—real-time interaction between patients and the system in terms of system response to patient input; few studies have effectively assessed the systems' usability and feasibility to determine how well patients understand and can adopt the technology involved. DialBetics is composed of 4 modules: (1) data transmission module, (2) evaluation module, (3) communication module, and (4) dietary evaluation module. A 3-month randomized study was designed to assess the safety and usability of a remote health-data monitoring system, and especially its impact on modifying patient lifestyles to improve diabetes self-management and, thus, clinical outcomes. Fifty-four type 2 diabetes patients were randomly divided into 2 groups, 27 in the DialBetics group and 27 in the non-DialBetics control group. HbA1c and fasting blood sugar (FBS) values declined significantly in the DialBetics group: HbA1c decreased an average of 0.4% (from 7.1 ± 1.0% to 6.7 ± 0.7%) compared with an average increase of 0.1% in the non-DialBetics group (from 7.0 ± 0.9% to 7.1 ± 1.1%) ( P = .015); The DialBetics group FBS decreased an average of 5.5 mg/dl compared with a non-DialBetics group average increase of 16.9 mg/dl ( P = .019). BMI improvement—although not statistically significant because of the small sample size—was greater in the DialBetics group. DialBetics was shown to be a feasible and an effective tool for improving HbA1c by providing patients with real-time support based on their measurements and inputs.